Congregational Obedience to the Commands of the Lord Jesus Based on John 15:9–17 - Yeremia; Desi Krisna Sari; Jhon Wesley (Gereja Alkitab Anugerah Kadoudan, 2025)
Obedience to the commands of the Lord Jesus is the primary calling for every follower of Christ. Based on John 15:9-17, this obedience is manifested in mutual love, abiding in Christ's love, and bearing fruit. This study aims to determine the level of confirmation of the apostle John's teaching on obedience to the commands of the Lord Jesus and to identify the most dominant dimensions in shaping the obedience of the congregation at the Sungai Yordan Philos Koli Church, Sanggau, West Kalimantan. The research used an explanatory quantitative method through surveys and interviews with 30 congregation respondents aged 24-50 years. The data were analyzed using Pearson's correlation test and one-way ANOVA test with the help of SPSS 25. The results of this study indicate that the level of obedience among congregations is moderate, while the dimension of mutual love is the most dominant factor in shaping obedience, with a correlation coefficient of 0.949 and a determination of 0.85 (90% contribution). This study confirms that true love is the main basis of obedience to the commands of the Lord Jesus, which is manifested through sacrifice and willingness to bear fruit for the glory of God.